Pembentukan Karakter Dalam Meningkatkan Kejujuran Berprestasi Mahasiswa Di Fakultas Psikologi Universitas Muhammadiyah Surakarta - Asiah, Siti (2016)
The phenomenon of cheating is one of the characters in the world of education, including in the academic fraud. Related cheating phenomenon that occurs among students, building the character of the student needs to be done, namely through character education. This research aims to describes the implementation of cultivating character education lectures to students and knowing the character formation about ways of thinking and honest behavior in achievement in Psychology Faculty of Muhammadiyah University of Surakarta. This research is qualitative research with case study research design. Implementation of research in Muhammadiyah University of Surakarta. Data was collected by interview, observation and documentation. Data analysis technique using an interactive model of analysis. Results of this research concluded that: 1) The implementation of cultivating character education in Psychology Faculty of Muhammadiyah University of Surakarta is an implementation of national education in order to develop the ability and character development as well as the civilization of student Muhammadiyah University of Surakarta. 2) Character building about ways of thinking and honest behavior in achievement in Psychology Faculty of Muhammadiyah University of Surakarta done by teaching to produce their own work, appreciate the work itself rather than the result of plagiarism, transfer goals into individual targets belonging to teachers by changing the students into individual student learning targets, so that students evaluate themselves, multiply tasks according to the priority level of difficulty of the course. The university leader, the rector, issued a decree for the enforcement of honesty, as well as the use of Turnitin application that can reduce the number of student plagiarism. The university socialize scientific work as the work itself even though the number of pages slightly. At the lecture the lecturer gives lectures related to norms, namely the Islamic religion courses. The University also formed LPID (Institute for Development of Basic Sciences) field of Al Islam Kemuhammadiyahan.